Comprehensive strategies to minimize radiation exposure during Interventional electrophysiology procedures: state-of-the-art review. (1st November 2020) - Desai, Miraj; Kahaly, Omar; Aslam, Adil; Saifa-Bonsu, Jonnie; Usmani, Maham; Okabe, Toshimasa; Afzal, Muhammad R.; Houmsse, Mahmoud
ABSTRACT: Introduction: Cardiac electrophysiology (EP) procedures are frequently performed in patients with cardiac arrhythmias, chronic heart failure, and sudden cardiac death. Most EP procedures involve fluoroscopy, which results in radiation exposure to physicians, patients, and EP lab staff. Accumulated radiation exposure is a known health detriment to patients and physicians. Area covered: This review will summarize radiation exposure, dose metrics, complications of radiation exposure, factors affecting radiation exposure, minimizing radiation exposure, zero or near-zero fluoroscopy strategies, and up-to-date research in the area of reducing radiation exposure and best practices. Expert commentary: Comprehensive strategies should be implemented in EP laboratories to minimize radiation exposure with standard fluoroscopy. There are routine techniques that can mitigate significant amounts of radiation exposure using standard equipment within the EP lab. The operators need to emphasize that EP practices routinely incorporate non-ionizing radiation sources for cardiac imaging (e.g. magnetic resonance imaging, advanced electroanatomical mapping systems, intracardiac ultrasonography) in addition to other novel technologies to mitigate radiation exposure to patients and physicians.